Building an Adaptive Islamic Organizational Culture in Madrasahs: Conceptual Analysis and Implementation Based on the Literature - Lutfi Hakim (Samarinda International Journal of Islamic Studies (SIJIS), 2025)
This article explores the crucial need for adaptive Islamic organizational culture within Madrasahs, the Islamic educational institutions in Indonesia. The study aims to analyze the conceptual underpinnings of building such a culture and to examine its practical implementation based on existing literature. The methodology involves a comprehensive review of relevant scholarly works, focusing on key themes such as leadership, teacher development, curriculum design, and the integration of Islamic values with modern educational practices. The findings highlight the importance of transformational leadership, emphasizing the development of teachers' competencies (Syukkur & Fauzan, 2021), and the integration of digital literacy (Az Zafi et al., 2021). The research emphasizes the need for a balance between traditional Islamic values and the demands of the 21st century, including the challenges presented by the COVID-19 pandemic (Habibi et al., 2021). The conclusion underscores the necessity of a flexible and responsive organizational culture in Madrasahs to ensure relevance, resilience, and the effective transmission of Islamic values in a rapidly changing world. This study suggests that by adapting their organizational cultures, Madrasahs can better prepare students for the future while upholding their core religious and cultural missions.